Antimicrobial Activity and Identification The Compounds of Methanol Extract from The Pleurotus Ostreatus Fruiting Body - Prastiyanto, Muhammad Evy; darmwati, Sri; iswara, Arya; Setyaningtyas, Agnis; Trisnawati, Laily; Syafira, Anna (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2016)
Pleurotus ostreatus is an edible mushroom that also has potential as medicinal values. In this study, fruiting body of P. ostreatus was tested for its ability to inhibit the growth of fungi and bacteria. The fruiting body powder of P. ostreatus was extracted using methanol by maceration method. Analysis of this compound was done by using anisaldehid sulfuric acid, Dragendorff reagent, and FeCl3. Using the agar well diffusion technique, the extracts were tested for their antimicrobial activity against Staphylococcus aureus (Gram positive), Enterobacter aerogenes (Gram negative) and Candida albican (yeast). The spot results on TLC using crude extract of P. ostreatus is terpenoids. Zone of inhibition for the various extracts varied between 10.9 - 23.2 mm. Ten miligrams extract exhibit maximum antimicrobial activity against most of the tested pathogensÂ